Upaya Kepolisian Dalam Menanggulangi Tindak Pidana Pencurian Kendaraan Bermotor Roda Dua (Studi di Polsek Munte Kabupaten Karo) - Sembiring, Juwina Sherlinta Br; Hadiningrum, Sri (CV. Rayyan Dwi Bharata, 2024)
This research aims to knowing how the police handle the crime of theft of two-wheeled motorized vehicles is the aim of this investigation (Study at the Munte Police). Munte Police, located in Singgamanik Village, Munte District, Karo Regency, North Sumatra, is the location for this research. Qualitative descriptive research methodology was used in this research. Five members of the Munte Police and two residents of Munte Village were the five research subjects in this study. Primary and secondary data are two types of data used in research. The data analysis method uses interactive analysis stages, including data collection, data reduction, data presentation, and drawing conclusions. Based on the findings of the study, Munte Police use punitive and preventive measures in an effort to stop people from stealing two-wheeled motorized vehicles. The preventive efforts carried out by the Munte Police include integrating security with the community in the Munte District area, improving police performance through implementing a term evaluation system, and making banners that urge the public to be more careful and alert in all their actions. Munte Police conduct regular and sporadic raids in areas with high crime rates as part of its repressive measures, including by imposing punishments on perpetrators of theft of two-wheeled motorized vehicles. The Munte Police are making every effort to tackle the crime of two-wheeled motor vehicle theft that occurs in the Munte District area. The main aim is to reduce the quantity of these crimes and enable people to live safely and peacefully.